Analysis Weather to Instability Price of Large Red Chili Using Time Series Based Prediction: The Perspective of Price Fairness in Islamic Economics - Mochamad Lutfan Hafidullah; Saifuddin (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study was conducted to examine the influence of weather conditions on large red chili production and farmer-level price instability in Paiton District, considering that fluctuations in rainfall, temperature, and seasonal patterns often affect production and reduce farmers’ income. A quantitative approach was employed using primary data collected through questionnaires from 70 large red chili farmers and secondary data on historical weather and price records. The data were analyzed using validity and reliability tests, simple linear regression, and time series analysis to determine the relationship between weather conditions and price instability. The results reveal that weather conditions have a significant effect on price instability (p = 0.000), with a coefficient of determination of 52.5%, indicating that variations in weather contribute substantially to production changes and subsequent price fluctuations. By integrating weather-related variables with a time-series analytical approach, this study provides empirical evidence that enriches agricultural econometric research while offering practical implications for farmers in planning planting schedules, supporting policymakers in designing weather-based price stabilization strategies, and encouraging the development of early warning systems and weather-based price forecasting models.